Social Atmospheres: The Cultural Psychology of the “Šatrija” and “Trečias frontas” Societies - Kvietkauskas, Mindaugas (Colloquia, 2015)
Analyses of many controversial episodes in twentieth century Lithuanian literary history increasingly call not only for debates about political and social processes, and about ideological contexts, but for examination of the cultural psychology of that era. Drawing on psychohistorical and emotional history approaches opens up the path to a more integrated understanding of historical situations and motivations. The author of this article undertakes to reconstruct and compare two literary societies – the neo-Catholic “Šatrija” and the leftist “Trečias frontas” (“Third Front”) – and the atmosphere around them during the late 1920s and early 1930s. Following Walter Benjamin, the concept of atmosphere takes into account the quality of sociocultural situations and relates objective historical contexts to subjective psychological states. The interplay between sociocultural environment and individual feelings is also stressed in foundational works of cultural psychology: correlations between them reveal common societal codes (c.f. Richard Schweder, Jerome Bruner, Michael Cole, Vytautas Kavolis). The article draws on a number of key elements in cultural psychology – relationship to authority and institutions, spaces and practices integrating the collective, private platonic and erotic relations – to analyze the wealth of memoir material left by members of the groups and individuals close to them. The study makes it possible to more clearly identify the liberal-salon and revolutionary-bohemian atmospheres that were operating among the young Lithuanian intellectuals in the late 1920s and early 1930s and to grasp that members of both groups faced various mechanisms of political and psychological repression. Their relationships with these mechanisms marked the beginning of a period of identity crisis for the members of “Šatrija” and “Trečias frontas” and led some of them to make radical ideological choices during the 1940s.
Keywords: cultural psychology; personality; intentional world; literary society; “Šatrija”; “Trečias frontas”; salon; bohemia; repression; modernization